Професіоналізм діяльності та особистості керівників органів і підрозділів МВС України - Бойко-Бузиль, Ю. Ю.; Boiko-Buzyl, Yu. Yu.; Швець, Д. В.; Shvets, D. V. (Право і безпека. – 2017. – № 1 (64). – С. 119–124, 2017)
Здійснено психологічний аналіз сутності та визначено специфічні особливості категорії професіоналізму в психолого-педагогічній науці. Розкрито зміст професіоналізму як результату діяльності та як властивості особистості. Охарактеризовано дві взаємообумовлені діалектичні єдності професіоналізму – професіоналізм діяльності та професіоналізм особистості. Узагальнено суттєві ознаки професіоналізму керівників органів і підрозділів МВС України. Зроблено акцент на важливості професіоналізму як детермінанти успішного виконання професійної управлінської діяльності.

The problem of researching the professionalism of the managers of the agencies and departments of the Ministry of Internal Affairs of Ukraine is particularly significant, considering their personal responsibility for the implementation of keeping the rights and freedoms of men and citizens, protection of human life and health, fighting against crime and guaranteeing public order in the country. The quality of any work depends on the fact, who organizes it, and growth, the extent and success of management activities depend on the level of the professionalism of the subjects of management process. The concept of the professionalism in its retrospective is young, and in the psychological content is daily one, it is often understood as “better” implementation of labor activities and associated with a particular profession or identified with skills, competence, expression of the activities results. According to the authors, the professionalism should be considered in dialectical unity of the activity and personality, where the professional’s personality is formed and developed in the process of professionalism’s development. Analyzed by the authors category of the professionalism, Rubinshtein understanding of the personality within its activities and the model of the personality, which includes “want”, “can”, “I myself”, formed the basis for understanding the professionalism of the managers of the agencies and departments of the Ministry of Internal Affairs of Ukraine as the finalizing period of the professional and personal development, which includes the professionalism of the professional and management activities and the professionalism of the manager as a personality on the way to professional and personal of acme tops. It has been indicated that the professionalism of the activities – is the result of professional management activities, covering professional success, professional interaction and professional position. The professionalism of the personality – is the integral property of a person, which is formed in the course of professional management activity and includes professional orientation, professional skills and professional character. However, the professionalism of the activity and the professionalism of the personality of a manager of the agencies and departments of the Ministry of Internal Affairs may be differentially assessed and accompanied by specially organized measures.

Осуществлён психологический анализ сущности и определены специфические особенности категории профессионализма в психолого-педагогической науке. Раскрыто содержание профессионализма как результата деятельности и как особенности личности. Охарактеризованы два взаимообусловленные диалектические единства профессионализма – профессионализм деятельности и профессионализм личности. Обобщены существенные признаки профессионализма руководителей органов и подразделений МВД Украины. Сделан акцент на важности профессионализма как детерминанты успешного выполнения профессиональной управленческой деятельности.
The professionalism of the activities and managers’ personality of the agencies and departments of the Ministry of Internal Affairs of Ukraine
Бойко-Бузиль Ю. Ю. Професіоналізм діяльності та особистості керівників органів і підрозділів МВС України / Ю. Ю. Бойко-Бузиль, Д. В. Швець // Право і безпека. – 2017. – № 1 (64). – С. 119–124.
Бойко-Бузиль Ю. Ю., Швець Д. В. "Професіоналізм діяльності та особистості керівників органів і підрозділів МВС України." Право і Безпека 1 (2017): 119-124.
Boiko-Buzyl, Yu.Yu. and Shvets, D.V. (2017), “The professionalism of the activities and managers’ personality of the agencies and departments of the Ministry of Internal Affairs of Ukraine” [“Profesionalizm diialnosti ta osobystosti kerivnykiv orhaniv i pidrozdiliv MVS Ukrainy”], Pravo i Bezpeka, No. 1, pp. 119–124.
Keywords: Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; професіоналізм; особистість; професійна управлінська діяльність; керівники органів внутрішніх справ; органи і підрозділи МВС України; professionalism; personality; professional management activities; manager; керівник; agencies and units of the Ministry of Internal Affairs of Ukraine; профессионализм; личность; профессиональная управленческая деятельность; руководитель; руководители органов внутренних дел; органы и подразделения МВД Украины